2019
DOI: 10.1503/cmaj.190337
|View full text |Cite
|
Sign up to set email alerts
|

Risk of rhabdomyolysis with donepezil compared with rivastigmine or galantamine: a population-based cohort study

Abstract: BACKGROUND: Donepezil, rivastigmine and galantamine are popular cholinesterase inhibitors used to manage the symptoms of Alzheimer disease and other dementias; regulatory agencies in several countries warn about a possible risk of rhabdomyolysis with donepezil, based on information from case reports. Our goal was to investigate the 30-day risk of admission to hospital with rhabdomyolysis associated with initiating donepezil versus other cholinesterase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…171 Rhabdomyolysis and neuroleptic malignant syndromes are uncommon side effects which have been reported in older adults receiving donepezil. [173][174][175] Furthermore, hemolytic anemia, syndrome of inappropriate antidiuretic hormone (SIADH), 161 and severe hepatitis 176 also present as uncommon adverse effects in clinical practice. AChEI-induced adverse effects may provide chance for prescribing cascades.…”
Section: Uncommon Adverse Effectsmentioning
confidence: 99%
“…171 Rhabdomyolysis and neuroleptic malignant syndromes are uncommon side effects which have been reported in older adults receiving donepezil. [173][174][175] Furthermore, hemolytic anemia, syndrome of inappropriate antidiuretic hormone (SIADH), 161 and severe hepatitis 176 also present as uncommon adverse effects in clinical practice. AChEI-induced adverse effects may provide chance for prescribing cascades.…”
Section: Uncommon Adverse Effectsmentioning
confidence: 99%
“…Fleet et al in 2019, for example, found that "donepezil was associated with a higher risk of hospital admission [for] rhabdomyolysis compared [to] rivastigmine or galantamine," with the rationale of the study being based upon a Health Canada alert for donepezil. 10 Post-marketing surveillance may indicate there are important differences within AChEIs with regards to safety. Among other emerging adverse effects that have arisen in recent years is the potentially fatal arrhythmia that can result from donepezil.…”
Section: Efficacy and Safety Differences Between The Three Acetylcholinesterase Inhibitorsmentioning
confidence: 99%
“…6 Although there are no proven modalities to prevent AD, healthy diet, physical activity, omega-3 fatty acid supplementation, cognitive engagement, and low alcohol consumption have also shown potential in this area. [7][8][9] Medications used for treatment of AD include cholinesterase inhibitors and partial N-methyl-D-aspartate (NMDA) antagonists, which modulate either acetylcholine or glutamate (Table 1 [10][11][12][13][14][15][16][17][18][19] ). Donepezil, rivastigmine, and galantamine are cholinesterase inhibitors used for treatment of mild to moderate disease.…”
mentioning
confidence: 99%
“…11 A recent population-based cohort study found that initiating donepezil is associated with a higher 30-day risk of admission to hospital due to rhabdomyolysis when compared to rivastigmine or galantamine. 12 This risk, however, has been estimated to be low. 12 In general, only 1 cholinesterase inhibitor should be tried at a time, and centrally acting anticholinergic medications such as diphenhydramine, tricyclic antidepressants, and oxybutynin should be avoided because these counteract the effects of the cholinesterase inhibitors.…”
mentioning
confidence: 99%
See 1 more Smart Citation